Introducing transformation twins in titanium alloys: an evolution of α-variants during additive manufacturing. Issue 3 (4th March 2021) - Wang, H.; Chao, Q.; Yang, L.; Cabral, M.; Song, Z. Z.; Wang, B. Y.; Primig, S.; Xu, W.; Chen, Z. B.; Ringer, S. P.; Liao, X. Z.
Abstract : Titanium alloys can experience a cooling-induced phase transformation from a body-centred cubic phase into a hexagonal close-packed phase which occurs in 12 crystallographically equivalent variants. Among them, variant selection II, 60°/ 1 2 ¯ 10, is very close to the orientation of { 10 1 ¯ 1 } 1 2 ¯ 10 twins (57.42°/ 1 2 ¯ 10 ). We propose that the cyclic thermal loading during additive manufacturing introduces large thermal stresses at high temperature, enabling grain reorientation that transforms the 60°/ 1 2 ¯ 10 variant boundaries into the more energetically stable 57.42°/ 1 2 ¯ 10 twin boundaries. This transformation twinning phenomenon follows a strain accommodation mechanism and the resulting boundary structure benefits the mechanical properties and thermal stability of titanium alloys. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: A new twinning mechanism, transformation twinning, was discovered in a Ti–6Al–4V alloy fabricated by selective laser melting. The resulting high density of transformation twins impact the global mechanical properties significantly.